2019
DOI: 10.1007/s00392-019-01546-3
|View full text |Cite
|
Sign up to set email alerts
|

The SAPPHIRE criteria, history of myocardial infarction and diabetes predict adverse outcomes following carotid endarterectomy similar to stenting

Abstract: Aims Identifying factors associated with worse outcome following carotid endarterectomy (CEA) is important to improve prevention of major adverse cardiovascular and cerebrovascular events (MACCE), yet rarely used for registries. We intended to identify predictors of MACCE following CEA as recently analysed for stenting. Methods and results Patients undergoing CEA at 2 centers over 13 years were entered into a database. Baseline clinical characteristics, procedural factors and a panel of clinical and lesion-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…The Stenting and Angioplasty with Protection in Patients at High Risk for Endarterectomy (SAPPHIRE) trial 21 found that a history of MI and diabetes was a high-risk factor for major adverse cardiovascular and cerebrovascular events. Consequently, that research team recommended increased attention for patients with such a history.…”
Section: Discussionmentioning
confidence: 99%
“…The Stenting and Angioplasty with Protection in Patients at High Risk for Endarterectomy (SAPPHIRE) trial 21 found that a history of MI and diabetes was a high-risk factor for major adverse cardiovascular and cerebrovascular events. Consequently, that research team recommended increased attention for patients with such a history.…”
Section: Discussionmentioning
confidence: 99%
“…Some prior studies reported sufficient predictive values, especially for identifying high-grade ICAS using direct measurement of NASCET percentage stenosis within 2-D color-Doppler overlays on gray-scale frames (Beebe et al 1999;Koga et al 2001). However, 2-D color-Doppler morphometry has not gained general acceptance for routine stenosis quantification partly because of inconsistent results and missing evidence for an advantage over hemodynamic stenosis grading with spectral blood velocity-based DUS measurements (Grant et al 2000(Grant et al , 2003Wardlaw et al 2005Wardlaw et al , 2006Brott et al 2011;Macharzina et al 2015Macharzina et al , 2019. Some recent publications suggest the application of Duplex blood velocities together with indirect and semiquantitative morphometric parameters for stenosis quantification; however, a clinically relevant improvement of sensitivity and specificity to detect 70% stenoses could not be substantiated for a multiparametric approach (Arning el al.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to symptomatic status, it is important to categorize ICAS at 50% and 70% accurately for guideline conform decision making in our daily routine practice (Barnett et al 1998;Grant et al 2003;Nicolaides et al 2010;Brott et al 2011;Macharzina et al 2015;Aboyans et al 2018). It has been suggested that patients diagnosed with non-progressive asymptomatic <70% stenosis benefit more from best medical therapy, and those with symptomatic >50% stenosis, from revascularization; however, clinical risk factors and vulnerability of the stenosis may need to be considered for individual stratification (Barnett et al 1998;Abbott 2009;Nicolaides et al 2010;Brott et al 2011;Macharzina et al 2015Macharzina et al , 2019Aboyans et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In the SAPPHIRE (Stenting and Angioplasty with Protection in Patients at High Risk for Endarterectomy) trial (748 operations; follow-up: 13 years), previous myocardial infarction (MI) (HR 2.045, 95% CI: 1.108-3.777, P=0.022), DM (HR 2.111, 95% CI: 1.183-3.767, P=0.011) and symptomatic patients [previous stroke or transient ischaemic attack (TIA); HR 2.045, 95% CI: 1.018-4.109, P=0.044] were independently associated with major adverse CV and cerebrovascular events (MACCE) (27).…”
Section: Dm and Carotid Endarterectomy (Cea) And Carotid Artery Stenting (Cas)mentioning
confidence: 99%